Towards a new approach for Seasonal Climate Forecasting in West Africa - Houngnibo, Mandela C.; Ali, Abdou; Gadédjisso-Tossou, Agossou; Mohamed, Hamatan; Agali, Alhassane; Minoungou, Bernard; Quenum, Narcisse; Segnon, Alcade C; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
West African Regional Climate Outlook Forums (RCOF) help end-users minimize climate-related risks and maximize benefits in different sectors. However, the current RCOF process or approach for generating climate information is subject to some shortcomings. To improve seasonal forecasting in West Africa, it is suggested that advances in computer technology, improved climate models, and the availability of products from several global climate centers be leveraged to develop an objective integrated seasonal forecasting process that will serve as a reference for the West African RCOF.